Improved Cardiopulmonary Resuscitation Performance With CODE ACES2: A Resuscitation Quality Bundle. Issue 24 (18th December 2018) - Hunt, Elizabeth A.; Jeffers, Justin; McNamara, LeAnn; Newton, Heather; Ford, Kenneth; Bernier, Meghan; Tucker, Elizabeth W.; Jones, Kareen; O'Brien, Caitlin; Dodge, Pamela; Vanderwagen, Sarah; Salamone, Cheryl; et al.
Abstract : Background: Over 6000 children have an in‐hospital cardiac arrest in the United States annually. Most will not survive to discharge, with significant variability in survival across hospitals suggesting improvement in resuscitation performance can save lives. Methods and Results: A prospective observational study of quality of chest compressions (CC) during pediatric in‐hospital cardiac arrest associated with development and implementation of a resuscitation quality bundle. Objectives were to: 1) implement a debriefing program, 2) identify impediments to delivering high quality CC, 3) develop a resuscitation quality bundle, and 4) measure the impact of the resuscitation quality bundle on compliance with American Heart Association (AHA) Pediatric Advanced Life Support CC guidelines over time. Logistic regression was used to assess the relationship between compliance and year of event, adjusting for age and weight. Over 3 years, 317 consecutive cardiac arrests were debriefed, 38% (119/317) had CC data captured via defibrillator‐based accelerometer pads, data capture increasing over time: (2013:13% [12/92] versus 2014:43% [44/102] versus 2015:51% [63/123], P <0.001). There were 2135 1‐minute cardiopulmonary resuscitation (CPR) epoch data available for analysis, (2013:152 versus 2014:922 versus 2015:1061, P <0.001). Performance mitigating themes were identified and evolved into the resuscitation quality bundle entitled CPR Coaching, Objective‐Data Evaluation, Action‐linked‐phrases, Choreography, Ergonomics, Structured debriefing and Simulation (CODE ACES 2 ). The adjusted marginal probability of a CC epoch meeting the criteria for excellent CPR (compliant for rate, depth, and chest compression fraction) in 2015, after CPR Coaching, Objective‐Data Evaluation, Action‐linked‐phrases, Choreography, Ergonomics, Structured debriefing and Simulation was developed and implemented, was 44.3% (35.3–53.3) versus 19.9%(6.9–32.9) in 2013; (odds ratio 3.2 [95% confidence interval:1.3–8.1], P =0.01). Conclusions: CODE ACES 2 was associated with progressively increased compliance with AHA CPR guidelines during in‐hospital cardiac arrest.